Lipid Profile Abnormalities among Patients with Diabetes Mellitus Type II, Presented at Tertiary Care Hospital - Nadeem Memon, Shabnam Rani, Rajkumar, Dolat Singh, Majida Memon, Muneer Sadiq, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the lipid profile abnormalities among diabetes patients presented at tertiary care Hospital. Methods: This cross-sectionals study was done at medicine out patient’s department (OPD) at Muhammad Medical College Mirpur-Khas, from September 2020 to September 2021. Patients of type II diabetes mellitus, presented at medicine OPD, aged more than 40 years, diabetes duration more than three years and both genders were included. A five ml blood sample was obtained in fasting from each case and sent to the Hospital laboratory to assess the HbA1c and lipid profile. All the data was collected via a structured study proforma, and the analysis was done using SPSS version 20. Results: In this study, 67 known diabetic patients were studied to observe the frequency of lipid profile abnormalities. Patient’s mean age was 51.64+10.32 years, mean BMI was 25.20+3.23 kg/m2 and mean Hba1c was 7.84+2.94%. Males were in majority 61.2% and females were 38.8%. Out of all 56.7% patients had lipid profile abnormalities. There was a positive correlation between hba1c and triglyceride level and a significant positive correlation between hba1c and total cholesterol level (r = 0.431, p = 0.001). Frequency of lipid profile abnormalities was statistically insignificant according to gender and duration of disease (p=>0.05). Conclusion: Lipid profile abnormalities were observed to be highly frequent among patients with type II diabetes mellitus. The early identification and treatment of dyslipidemia in individuals with DM seems to be a significant aspect of lowering the risk of DM-related morbidity and mortality. Keywords: Diabetes type II, lipid profile, Hba1c